Robust strain measurement on deformation-roughened microscopic surfaces with fluorescent marker imaging - Raeissi, Mona. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2018., 2018)
Digital image correlation (DIC) implemented at microstructural length-scales of materials with microscopic imaging has emerged as an important tool to investigate the fundamental mechanisms of deformation. An important problem in the optical implementation of microscopic DIC is the fact that deformation itself can create surface features. These compromise the DIC pattern used for tracking material sub sets and cause errors and invalidations. A strategy to overcome DIC invalidations on deformation-roughening structures is to create a deformation mode that ﬁlters the mi crostructure out of the images and simply tracks introduced tracing particles. In this study, ﬂuorescent microscopy is investigated as a viable imaging method to achieve this goal. Fluorescent pattern application has been developed with spraying and spin-casting techniques using both ﬂuorescent DAPI (4’,6-Diamidino-2-Phenylindole, Dihydrochloride) solution and ﬂuorescent beads. Beads that are spread on the sur face with spin casting yielded consistent patterns that act suﬃciently robust in DIC method. In the in situ loading experiments, ﬂuorescent imaging (FDIC) line has been used in parallel to a routine optical microscopy line that has the same magniﬁcation to precisely determine and quantify the beneﬁts as well as limitations of the ﬂuorescence application. Two material conﬁgurations of as-cast and extruded Magnesium, both intended to favor formation of large twins, has been used in these in situ microscopic DIC+FDIC experiments. The results show that the premise of the FDIC method is viable, namely, while DIC is invalidated in certain twinned material neighborhoods, FDIC maintains producing consistent results.
Keywords: Digital image correlation.